Etnomatemática e calendário agrícola da comunidade quilombola São Pedro - OLIVEIRA, Hermes Reinaldo de (2022)
This mathematics course conclusion work has as its theme Ethnomathematics and the Agricultural Calendar of the Ribeirinha and Quilombola São Pedro community. It is the result of an interaction between a bibliographic research and a field research whose objective is to obtain an understanding of how the agricultural calendar works in the practice of family farming in this community, establishing a period for planting, harvesting and the amount of crops harvested in given area, that is, the amount of genus that each farmer can harvest per task, hectare or bushel planted. The work is justified by the small amount of research in this area in which science and the mathematical knowledge of a people are combined. The focus is on how ancient peoples measured things, in a rudimentary time, how mathematics is present in people's daily lives and how ethnomathematics can help to understand the knowledge generated in communities over the centuries. The methodology used will be bibliographic, quantitative and documentary; the collection of information on the topic, validated through analysis of results and discussions. The fundamental contribution of this study is to show that the production of knowledge occurs in all human cultures. The intention is to value the knowledge produced by the Ribeirinhas and Quilombola communities, which will contribute to the enrichment of the universal mathematical heritage.